PENGALAMAN DALAM MENGHADAPI SINDROM PRA MENSTRUASI PADA REMAJA PUTRI - Maria Floriana Ping; Elfina Natalia (Husada Mahakam, 2022)
Premenstrual syndrome (PMS) includes clinically significant somatic and psychological manifestations during the luteal phase of the menstrual cycle, causing substantial distress and reduced functional capacity. This study aims to determine the experience of young women in dealing with the symptoms of premenstrual syndrome they are experiencing. This study uses a qualitative study with a phenomenological design. The number of samples in this study were 8 participants. The inclusion criteria were families with family members who had recurrent strokes. Data collection uses in-depth interviews. Data analysis uses thematic analysis. This study obtained four themes, namely Theme 1) symptoms of premenstrual syndrome experienced by respondents. Theme 2) actions taken to treat premenstrual syndrome symptoms. Theme 3) Use of non-pharmacological therapies to treat premenstrual syndrome. Theme 4) Factors influencing premenstrual syndrome treatment. each respondent has premenstrual syndrome treatment that is tailored to the symptoms experienced, young women feel the need to be exposed to a more diverse selection of non-pharmacological therapies as well as specific treatment of psychological symptoms